(untitled) (Journal of Medicine, 2017)
Star fruit (Averrhoa carambola) is a commonly available and popular fruit in many tropical and subtropical countries. Although star fruit induced oxalate nephropathy in patients with pre-existing renal impairment is well documented, reports on its effect on those with normal renal function are infrequent. Hereby we report a case where a young man with previously normal renal function presented with AKI that was attributable to consumption of star fruit. This write up illustrates the importance of obtaining the patient’s history with respect to ingestion of star fruit in case of sudden and unexplained development of renal impairment. J MEDICINE Jan 2018; 19 (1) : 63-65